Periclimenes sarkanae sp. nov. a new pontoniine shrimp from Moreton Bay, Queensland (Crustacea: Decapoda: Palaemonidae) - Bruce, A.j. (Zootaxa, 2007)
A new species of pontoniine shrimp, Periclimenes sarkanae sp. nov., from southern Queensland sea grass beds, is described and illustrated.. The new species is a member of the obscurus species-group and is most closely related to P. obscurus Kemp. Its associations, if any, are unknown.